ANALISIS PENGARUH TINGKAT SUKU BUNGA (BI RATE), BAGI HASIL, INFLASI DAN HARGA EMAS TERHADAP JUMLAH DEPOSITOMUDHARABAH PERBANKAN SYARIAH PERIODE 2010-2015 - Asmawarna Sinaga (Journal Analytica Islamica, 2016)
The purpose of this research to determine how big the influence of BI Rate, Profit Sharing, Inflation and Gold Price against Total of Deposits. The samples used in this research are data of BI Rate, Profit Sharing, Inflation, Gold Price and Mudharabah Deposits(a period of one month) from January 2010 to June 2015.This research used quantitative research approach which is VAR. Profit Sharing variable is the most dominant influence among other variables to Mudharabah Deposits amounted to7.19%. Inflation variable is the most dominant influence among other variables to Total of Mudharabah Deposits amounted to26.95%. BI Rate Variable has influence to Mudharabah Deposits amounted to 3.55% and the Gold Price variable has influence to Mudharabah Deposits amounted to 0.71% .